From silos to synergies: multisectoral collaboration to reach the last mile of malaria elimination in India - Shinde, Shwetangi R.; Shah, Anuradha K. (International Journal Of Community Medicine And Public Health, 2024)
Malaria, a public health problem in India with declining endemicity, is now being tackled with the National Strategic Plan for Malaria Elimination (2023-2027), targeting zero indigenous cases by 2027 and complete elimination by 2030. A central pillar of this strategy is vector control, yet its effectiveness is undermined by siloed efforts, where different sectors work in isolation. Malaria is a disease with various environmental, social, and behavioural determinants, requiring a multisectoral approach for control. Coordinated efforts involving the health, environment, agriculture, housing, water, and education sectors among others are crucial to address the broader determinants of mosquito breeding and disease transmission. Focusing exclusively on health sector interventions risks overlooking these critical factors. Multisectoral collaboration for vector control is central to the global vector control response (GVCR) 2017-2030, the multisectoral approach to the prevention and control of vector-borne diseases (2020), along with India's manual on integrated vector management. Several ministries have already begun implementing measures to address mosquito breeding. Successful case studies from Kenya, Maharashtra, and Gujarat demonstrate the effectiveness of such collaborative efforts in vector control. However, challenges remain, particularly in defining roles, securing funding and strengthening entomological infrastructure. Addressing these challenges through strong political commitment, clear accountability frameworks, and increased resources is crucial for achieving sustainable malaria elimination in India. Improving health outcomes should be a shared responsibility, breaking silos and aligning efforts across all sectors and sections of the society.